Examining the Relationship between Broadband Access, Parent Technology Beliefs, and Student Academic Outcomes - Zhexun Xin; Damian Bebell; Gareth Cleveland (MDPI AG, 2024)
This study explores the relationship between community broadband access, parent technology use and beliefs, and student academic outcomes in a Southeastern U.S. school district during and after the COVID-19 pandemic. By applying a quantitative exploratory approach and multiple regression analysis, the research revealed that parents' technology beliefs and use were significantly associated with students' standardized Math and ELA scores. While parents' positive beliefs about technology's developmental impact showed an inverse relationship with student performance, greater concerns about familial challenges related to technology were associated with lower scores. The results explored persistent social inequities, whereby students who were identified as Black historically score lower than White-identified students, emphasizing the role and importance of digital equity to mitigate disparities and enhance outcomes. Both the methodology and results encourage researchers, educational leaders, and policymakers to deeply consider the role of parental access to and engagement with digital resources, and how they contribute to shaping student outcomes.